Análise dinâmica de estruturas de aço suportes de máquinas rotativas - Ferro, Rafael Marin (2014)
Adequate dynamic analysis is needed to check for Support Frame Structures of mechanical equipment to ensure not only the human user comfort as well as good conditions for the operation of equipment structure. Recent studies of Structural Dynamics and Dynamics of equipment see the difficulty in performing real models of Support Frame Structures of Rotating Machinery. Booth areas have in common study Analysis of Vibrations produced by Dynamic Loads is necessary a study comparing the two areas, which are considered the dynamic loads caused by rotating machinery in checking Support Frame Structures.. This thesis is based on a survey of the real operating conditions of Rotating Machines such as pumps, compressors and fans, targeting the correct application of Dynamic Loads produced by the equipment applied in Support Frame Structures. With the data of speed, acceleration, frequency and consequently vibration, the set will be generated Computational models of Support Frame Structures. Models of Structures with loads of equipment applied, carried out with the aid of software strap. Will be generated, in Dynamic Module, models of Support Frame Structures with connections rigid, pinned or semi-rigid. Varying loads of a model of Rotating Machinery, this study will use a centrifugal pump we can see which have the best Support Frame and Performance with enhanced reliability in relation structure versus vibration. For the purpose of design models, we use Support Frame Structures of rotating machines used in real Industries models.